2016
DOI: 10.1101/lm.042010.116
|View full text |Cite
|
Sign up to set email alerts
|

Positivity effect specific to older adults with subclinical memory impairment

Abstract: Numerous studies have suggested that older adults preferentially remember positive information ("positivity effect"), however others have reported mixed results. One potential source of conflict is that aging is not a unitary phenomenon and individual differences exist. We modified a standard neuropsychological test to vary emotional content and tested memory at three time points (immediate/20 min/1 wk). Cognitively normal older adults were stratified into those with and without subclinical memory impairment. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 41 publications
1
12
0
Order By: Relevance
“…2B, comparing positive-high arousal and negative-low arousal bars). In a broader sense, these results contribute to the literature of preserved emotion processing in late life, and memory preferences for positive information in healthy older adults (reviewed by Reed, Chan, and Mikels, 2014), and individuals with MCI (Callahan et al, 2016; Gorenc-Mahmutaj et al, 2015; Leal et al, 2016). …”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…2B, comparing positive-high arousal and negative-low arousal bars). In a broader sense, these results contribute to the literature of preserved emotion processing in late life, and memory preferences for positive information in healthy older adults (reviewed by Reed, Chan, and Mikels, 2014), and individuals with MCI (Callahan et al, 2016; Gorenc-Mahmutaj et al, 2015; Leal et al, 2016). …”
Section: Discussionmentioning
confidence: 53%
“…Moreover, examining recall in addition to recognition could further probe the nuances of memory decline in healthy older adults and MCI patients. A recent study reported that individuals with below-average episodic memory preferentially recalled the gist of positive stories relative to individuals with above-average episodic memory, although this effect did not extend to memory for story details (Leal et al, 2016). This raises the question of whether the patterns of emotional scene memory in healthy older adults and MCI patients would appear to differ if recall or gist were assessed as well as recognition of specific scene items and backgrounds.…”
Section: Discussionmentioning
confidence: 98%
“…We suspected that our experimental approaches tapped into ubiquitous goals in daily life; in other words, all things being equal, older people favor positive material. In studies where experimenters assigned new goals, however, and participants were asked to attend specifically to certain types of information and operate on the information (for example, [55]), preferential processing of positive materials was diminished (see [9]).…”
Section: Failures To Replicate the Positivity Effectmentioning
confidence: 99%
“…An emotional or a neutral narrative is played over the slides to color participants` interpretation of what they are seeing: In the emotional version, the child is hit by a car en route. Other materials following a similar logic have also been developed (Leal et al, 2016). Available stimuli of these nature are, however, often limited to one neutral version and one emotional version (although for a recent innovation, see Kim et al, 2013).…”
Section: Experimenter-generated Stimulimentioning
confidence: 99%